2017
DOI: 10.1016/j.cma.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Approximate deconvolution reduced order modeling

Abstract: Highlights• A new large eddy simulation reduced order model (LES-ROM) framework.• A new approximate deconvolution ROM (AD-ROM) not of eddy viscosity type.• Successful application of AD-ROM to 3D flow past cylinder at Re = 1000. AbstractThis paper proposes a large eddy simulation reduced order model (LES-ROM) framework for the numerical simulation of convection-dominated flows. In this LES-ROM framework, the proper orthogonal decomposition (POD) is used to define the ROM basis and a ROM differential filter is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 59 publications
0
62
0
Order By: Relevance
“…In ROMs, spatial filtering has been used as a preprocessing step, to filter out the noise in the snapshot data and, thus, in the generation of the POD modes (see, e.g., Section 5 in [25] for a survey of relevant work). Two types of explicit ROM spatial filters are considered in this section: a POD projection (Section 3.1) and a POD DF (Section 3.2; see [37] for a related, but different, approach). Indeed, in the preprocessing spatial filtering used in [25], the snapshots (i.e., the input data) are spatially filtered, but the ROMs (i.e., the mathematical models) are not.…”
Section: The Galerkin Rom (G-rom)mentioning
confidence: 99%
See 1 more Smart Citation
“…In ROMs, spatial filtering has been used as a preprocessing step, to filter out the noise in the snapshot data and, thus, in the generation of the POD modes (see, e.g., Section 5 in [25] for a survey of relevant work). Two types of explicit ROM spatial filters are considered in this section: a POD projection (Section 3.1) and a POD DF (Section 3.2; see [37] for a related, but different, approach). Indeed, in the preprocessing spatial filtering used in [25], the snapshots (i.e., the input data) are spatially filtered, but the ROMs (i.e., the mathematical models) are not.…”
Section: The Galerkin Rom (G-rom)mentioning
confidence: 99%
“…In Reg-ROMs, on the other hand, some of the ROM terms are explicitly filtered, and thus, the mathematical model is modified. Two types of explicit ROM spatial filters are considered in this section: a POD projection (Section 3.1) and a POD DF (Section 3.2; see [37] for a related, but different, approach). The properties of these explicit ROM spatial filters are discussed in Section 3.3.…”
Section: The Galerkin Rom (G-rom)mentioning
confidence: 99%
“…However, it has been observed that the discarded modes often contribute to the evolving dynamics of large-scale complex turbulent flow systems, like the geophysical flows [36], resulting in instabilities and modeling errors in the solution [25,[37][38][39]. Thus, several research efforts have been devoted to improve the stability of ROM-GP frameworks by addressing the truncated modes contributions [40][41][42][43][44]. Noack et al [45] proposed an extra 'shift-mode' for accurate representation of the unstable steady solution.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize, however, that the F-ROM (18) is not a closed system of equations, since the ROM stress tensor SFS r (which is used in the definition of ; see (19)) depends on u d (see (17)). Thus, to close the F-ROM (18), we need to solve the ROM closure problem, 30,33,[59][60][61] ie, to find a formula ≈ (a). The explicit formula for (see (17) and (19)) allows for the first time the use of data-driven modeling of the entire missing ROM information.…”
Section: Data-driven Correction Rommentioning
confidence: 99%